Self-Esteem dengan Self-Presentation pada Mahasiswa Pengguna Media Sosial Instagram - Angelique Latupeirissa; Sutarto Wijono (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this study is to find out the relationship between self-esteem and self-presentation of Instagram users in students. The subject of this study is The Psychology Student of Satya Wacana Salatiga Christian University, the determination of the research subject was carried out by nonprobability sampling techniques, especially purposive sampling consisting of 143 students. The data collection technique in this study is to use quantitative methods using data collection measuring instruments using Roseberg's Self-Esteem Scale (RSES) (1965). RSES Self-Esteem measuring instrument, which has been translated by Azwar (2012) Both aspects have five dimensions, namely: academic, social, emotional, family, and physical dimensions and the self-presentation scale (Self-Presentation) modified by researchers based on the Self-Presentation Tactics Scale – Assertive (SPRS; Lee et all, (1999) consists of 38 items measuring Self-Presentation. The results of the calculation using spearman's rho correlation technique were followed by a coefficient value of 0.403; (p) = 0.430 (p > 0.05). This shows that there is a relationship between self-esteem and self-presentation of Students of Instagram users